2005
DOI: 10.1002/mc.20092
|View full text |Cite
|
Sign up to set email alerts
|

A paracrine signal mediates the cell transformation response to low dose gamma radiation in JB6 cells

Abstract: The carcinogenic response to radiation is complex and may involve adaptive cellular responses as well as a bystander effect mediated by paracrine or intercellular signaling activities. Using a newly developed co-culture model we have examined whether low dose gamma radiation induces the transformation of JB6 mouse epidermal cells as well as non-irradiated bystander cells. Cell transformation response is defined as the acquisition of anchorage-independent growth properties and is quantified by counting colonies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…We have previously demonstrated that ionizing radiation induces the transformation of JB6 mouse epidermal cells 6. As expected, a low dose of radiation (10 cGy) produces a small increase in cell transformation response (doubling–tripling of spontaneous background transformation frequency of ∼20 colonies/10 000 cells).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…We have previously demonstrated that ionizing radiation induces the transformation of JB6 mouse epidermal cells 6. As expected, a low dose of radiation (10 cGy) produces a small increase in cell transformation response (doubling–tripling of spontaneous background transformation frequency of ∼20 colonies/10 000 cells).…”
Section: Introductionsupporting
confidence: 70%
“…We examined endogenous murine DBP and HLF expression in colonies derived from irradiated JB6 cells 6 to determine whether central features of AIG regulation were conserved in colonies induced by low doses of radiation. Colonies spontaneously arising in control, 2 and 20 cGy irradiated dishes were isolated and established as cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced proliferation (14 -17%) has been reported following co-culture of unirradiated rat liver epithelial cells with cells exposed to 0.5 -10 Gy (Gerashchenko & Howell 2003). A significant increase in the number of bystander-specific colonies has also been observed when unirradiated JB6 cells were co-cultured with their low dose (10 cGy) irradiated counterparts as compared to that in cells co-cultured with sham exposed JB6 cells (Weber et al 2005). Increased proliferation response following co-culture of unirradiated neoplastic human salivary gland (HSG) cells with irradiated cells was related to the linear energy transfer (LET) as well as the radiation dose (Shao et al 2003).…”
Section: Discussionmentioning
confidence: 79%
“…Colony growth in soft agar is a well-established index of cell transformation [24]. Anchorage-independent growth was studied using the CytoSelect TM 96-Well Cell Transformation Assay kit (Cell Biolabs) according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to tumor initiation, tumor promotion is largely reversible, dependent on epigenetic mechanisms, and is a rate-limiting step in multi-stage carcinogenesis, making it an attractive target for anticancer drugs [20,21]. The JB6P + cells can be transformed to malignancy by tumor promoters, and hence, constitute an ideal model to identify anti-tumor promoting and chemopreventive agents and to decipher their mechanism of action [19,22-24]. …”
Section: Introductionmentioning
confidence: 99%